Comparison of Tc-99m pertechnetate images with dual-phase Tc 99m MIBI and SPECT images in primary hyperparathyroidism - Sager, Sait (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: The purpose of this study was to evaluate the value of Tc-99m pertechnetate planar, dual-phase MIBI and MIBI-SPECT images in the determination and localization of parathyroid lesions. MATERIALS AND METHODS: In this study, 38 patients who underwent operation for primary hyperparathyroidism were included. Tc-99m pertechnetate planar-pinhole imaging of the neck and then MIBI planar and SPECT images in supine position was performed. Late SPECT images were acquired 120 minutes after the injection. Early and late MIBI images were quantitatively evaluated. RESULTS: Of the 38 patients, 30 of them had adenoma, 2 patients had hyperplasia and 6 of them were normal on planar images. Thirty-four of 38 patients were positive on SPECT images. SPECT images of the patients with positive results were matched with pathology results. CONCLUSION: As a result, Tc-99m pertechnetate planar-pinhole, Tc-99m MIBI planar and SPECT images are useful for localization of parathyroid lesions especially in multinodular thyroid gland. However, US or CT images are necessary for more accurate localization and Tc-99m pertechnetate images are useful for interpreting and comparing with the early and late MIBI images.